The Role of the Church in Building Family Spirituality of Church Members - Ginting, Jamsen; Simanjuntak, Ferry; Suwandi, Markus (IJOSMAS, 2022)
The Covid-19 outbreak has changed human life, especially family spirituality. Church role to serve congregation and families experienced obstacles and changed the interaction between the church and the congregation from face-to-face interactions to infrequently distant interactions. The shocks in church services impacted church strategy in build spirituality of families and congregations that were not maximized and not consistent. The church needs time, money and energy in adapting to government regulations, following health protocols, maintaining the health of the congregation and continuing to serve the congregation within limitations. Paul's pastoral letter in Colossians 3:18-21, reminds all household members to carry out their respective roles according to God's word. Colossians letter became a guidance for families to continue to experience spiritual growth by making God as the Leader in the family. Colossians letter also as a guidance for church leaders to mobilize family worship of the congregation in building family spirituality. The church made a quick response to build families spirituality of church members by increasing church servant competence, providing technology facilities and infrastructure in serving the congregation. Through this study, the authors found the patterns of church worship and cell groups that developed through online worship. Family services have also begun to be carried out online with the active participation of family members. Colossians letter also as a guidance for church leaders to mobilize family worship of the congregation in building family spirituality. The church made a quick response to build families spirituality of church members by increasing church servant competence, providing technology facilities and infrastructure in serving the congregation. Through this study, the authors found the patterns of church worship and cell groups that developed through online worship. Family services have also begun to be carried out online with the active participation of family members. Colossians letter also as a guidance for church leaders to mobilize family worship of the congregation in building family spirituality. The church made a quick response to build families spirituality of church members by increasing church servant competence, providing technology facilities and infrastructure in serving the congregation. Through this study, the authors found the patterns of church worship and cell groups that developed through online worship. Family services have also begun to be carried out online with the active participation of family members. the authors found the patterns of church worship and cell groups that developed through online worship. Family services have also begun to be carried out online with the active participation of family members. the authors found the patterns of church worship and cell groups that developed through online worship. Family services have also begun to be carried out online with the active participation of family members.